Entrepreneurial Commercialization Choices and the Interaction between IPR and Competition Policy - Joshua S. Gans; Lars Persson (Research Institute of Industrial Economics (IFN), 2012)
This paper examines the interaction between intellectual property protection and competition policy on the choice of entrepreneurs with respect to commercialization as well as the rate of innovation. We find that stronger intellectual property protection makes it more likely that entrepreneurs will commercialize by cooperating with incumbents rather than competing with them. Consequently, we demonstrate that competition policy has a clearer role in promoting a higher rate of innovation in that event. Hence, we identify one reason why the strength of the two policies may be complements from the perspective of increasing the rate of entrepreneurial innovation.
Keywords: O31; 330; Entrepreneurs; Innovation; Commercialization; Intellectual property law; Competition law; Innovationsmanagement; Produktinnovation; Wettbewerbsrecht; Immaterialgüterrechte; EU-Staaten; USA